Frequency Doubling Technology Visual Field Loss in Fabry Subjects Related to Retinal Ganglion Cell Function as Explored by ERG and OSOME - Michaud L; Garon ML; Forcier P; Diaconu V (Clinical Ophthalmology, 2022)
Langis Michaud, Marie-Lou Garon, Pierre Forcier, Vasile Diaconu École d’optométrie de l’Université de Montréal, Montréal, CanadaCorrespondence: Langis Michaud, École d’optométrie de l’Université de Montréal, 3744 Jean-Brillant, Suite 260-15, Montréal, H3T 1P1, Canada, Tel +1-514-343-6111 ext 8945 ; Tel +1-514-343-6111 ext 8945, Email langis.michaud@umontreal.caPurpose: This study aims to evaluate potential causes of FDT visual field loss in a selected group of Fabry subjects.Patients and Methods: This is a pilot observational study. Subjects were assessed during 2 visits. The following tests were performed: visual acuity, tonometry, optical coherence tomography (OCT) optic nerve scan, frequency doubling time (FDT) and threshold (SAP) VF, ERG, and Online Spectro-reflectometry Oxygenation Measurement in the Eye (OSOME). Results are compared across visits and, when indicated, interpreted against those collected on non-Fabry population matched for age and sex.Results: The study population was composed of 3 males (34.3 ± 8.9 y.o.) and 5 females (46.4 ± 6.5 y.o). For all subjects, BCVA remained 6/6 OU throughout the study and OCT optic nerve scans were normal. FDT showed a defect in at least 1 quadrant for all participants, in contrast with SAP. FDT PSD value was found different vs SAP. For ERG, the i-wave (52.1 + 2.7 ms) and B-waves (31.6 ± 2.1 ms) peak times were significantly longer compared to a non-Fabry population (p < 0.05). Overall blood oxygenation varied from 61.3% ± 4% to 68.1% ± 4% at the second visit, suggesting a loss of capillary perfusion. Blood volume varied based on location (superior/inferior), eye tested (OD/OS) and time (visit 1/2). The range of values exceeds normal subjects findings (p < 0.05). Blood volume was correlated to FDT PSD value for the superior area of the optic nerve.Conclusion: The results suggest that Fabry subjects present FDT deficits and abnormal ERG patterns that may be explained by a retinal dysfunction affecting retinal ganglion cells (RGCs), second to vascular alterations.Keywords: Fabry disease, retinal ganglion cells, electroretinography, OSOME